A novel synthetic strategy of Fe-ZSM-35 with pure framework Fe species and its formation mechanism. Issue 8 (3rd July 2018) - Ju, Xiaohua; Tian, Fuping; Wang, Yanli; Fan, Fengtao; Feng, Zhaochi; Li, Can
Abstract : A novel two-step crystallization process of Fe-ZSM-35 zeolite was designed, and analyzed by UV resonance Raman spectroscopy. Abstract : Fe-ZSM-35, as a zeolite with ferrierite-like structure, is an important catalyst in industry, and it is usually very difficult to obtain through conventional methods. Understanding the semi-crystallized structure at the nanoscale is the key to control their properties and design the best materials for their ever increasing uses. Herein, we report a novel and controllable method for the synthesis of Fe-ZSM-35 with pure framework Fe species; the essence of this novel synthetic method is a two-step static hydrothermal process. Initially, semi-crystallized Fe-containing species and a semi-crystallized ZSM-35 structure are prepared, then the two semi-crystallized materials are mixed and crystallized to give Fe-ZSM-35 zeolite. This method can almost eliminate the retarding crystallization effect of hetero Fe and is beneficial for a high content of Fe to be incorporated into the ZSM-35 framework. The formation mechanism of Fe-ZSM-35 zeolite was also investigated by UV Raman spectroscopy in combination with X-ray powder diffraction and UV-vis diffuse reflectance spectroscopy. The studies indicate that the Fe-containing aluminate-silica gel was initially mixed with the semi-crystallized ZSM-35 structure fragments to generate the Fe-ZSM-35 structure, and this method may be extended to the other metal-hetero zeolites.